"I Don't Feel Like I Have a Problem Because I Can Still Go To Work and Function": Problem Recognition Among Persons With Substance Use Disorders. (10th November 2019) - Rogers, S. M.; Pinedo, M.; Villatoro, A. P.; Zemore, S. E.
Abstract: Background : Persons with substance use disorders (SUDs) who do not recognize their substance use as problematic are less likely to perceive needing treatment and less motivated to seek help. Factors that contribute to problem recognition among persons with SUDs are poorly understood. Objective : To explore in-depth factors that may explain why those who meet diagnostic criteria for SUDs do not perceive having a substance abuse problem. Methods : We recruited 54 participants with recent (i.e., past-5-year) SUD for qualitative interviews. Participants were recruited via online ads and screened for eligibility through an online survey. Interview questions focused on participants' alcohol and drug use behaviors, adverse consequences stemming from their substance use, past treatment use experiences, and barriers/reasons for not using specialty treatment. Interviews were thematically coded to identify prominent themes that may explain low problem recognition. Results : We identified two prominent themes that contributed to problem recognition: modifying substance use behaviors to avoid adverse consequences and stigma (i.e., "othering" ). Participants who (1) reported adjusting their alcohol and drug use in ways that would not interfere with important life responsibilities, especially work-responsibilities; (2) described those with alcohol and drug problems negatively; and (3) associated treatment with personal defeat were less likely to perceive having a SUD. Conclusions/Importance : These findings can be used to inform intervention strategies aimed at increasing problem recognition among persons with SUDs. Such strategies may facilitate motivation (i.e., desire for help and treatment readiness) to use and complete treatment, thereby reducing the unmet treatment gap among persons with SUDs.